Utilization of GPT-4 to Improve Education Quality Through Personalized Learning for Generation Z in Indonesia - Muhammad Fatihul Firdaus; Joseph Nugraha Wibawa; Fajri Fathur Rahman (IT for Society, 2023)
The Golden Generation or Generation Z, an  important part of the 2020-2035 demographic bonus, will face  unique educational challenges, such as low literacy rates and  uneven access to technology across regions[1]. To support the  potential implementation of personalized learning for  Generation Z in Indonesia, a research study was conducted to  investigate the potential use of GPT-4, an artificial intelligence  that uses the GPT language model and the latest Natural  Language Processing (NLP) technology. Quantitative,  qualitative, and literature study research methods were used to  evaluate the effectiveness and accuracy of GPT-4 in the  Indonesian educational context. Data was collected from  sample testing and reference to previous GPT-4 research, and  results were analyzed using predefined evaluation methods.  The results of the analysis showed that there was an  improvement in terms of coherence and knowledge with the  GPT-4 model compared to previous models. To maximize the  potential of GPT-4 in education, there needs to be strong  support from various parties, as well as efficient adaptation to  the specific needs of students and the educational environment  in Indonesia [2]. With an integrated approach, ethics, and  safety, GPT-4 has the potential to support inclusive and  effective education for Generation Z in Indonesia.